VD_FINDINFO HC / 2021 / 420 vom 28. Mai 2021 - VD Tribunal cantonal (2021)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, CONJOINT, REVENU HYPOTHÉTIQUE | 176 CC, 179 CC, 59 al. 2 let. e CPC (CH)